Sadie's sukkah breakfast ebook - Korngold, Jamie (Sukkot & Simchat Torah., 2011)
Waking up early in the morning on Sukkot, Sadie and Ori decide to serve breakfast in the sukkah. But when the table is set and the food is ready, they remember that a sukkah celebration needs guests. No one is awake, so who should they invite?